Optical Coefficients and PL Spectra with Variation in Ga-content in GaSeTe Thin Films: Visible Spectrum - Neeru Chaudhary; S.K. Tripathi; Navdeep Goyal (Журнал нано- та електронної фізики)
The optical properties (transmission and emission) for GaxSe85 – xTe15(x  0, 2, 6, 10, 15) semiconductor were studied using UV Visible spectra and PL Spectra of thermally evaporated thin films. Optical band gap is found to be decreasing with increased Ga-content in the compositions. Increase in refractive index, dielectric constants and absorption coefficient is observed in the wavelength region 550-850 nm.The fall in the optical band gap is explained with chemical bond approach and electro negativity. The increase in refractive index (n) is interpreted in association to the mean coordination number and cohesive energy. Direct band gap is found to be allowed in these thin films.